THE RELATIONSHIP BETWEEN SELF-TRUST AND PARENTAL SUPPORT WITH ENTREPRENEURIAL MOTIVATION OF STUDENTS IN CLASS XI AUTOMATION EXPERTISE AND OFFICE MANAGEMENT PROGRAM AT SMK N 2 MAGELANG - Annisa, Nenden Nur; Amallia, Fitria; Purwaningsri (CV ODIS, 2021)
The purpose of this study is to determine the relationship between self-confidence and parental support with entrepreneurial motivation in class XI students of automation and governance expertise program offices of SMK N 2 Magelang. This study used a sample of 102 students. The technique used in data collection in this study is to use saturated samples with a questionnaire or a questionnaire that contains three variables, namely self-confidence, parental support, and entrepreneurial motivation. The results of the study are to show there is a positive and significant relationship between self-confidence and parental support for the entrepreneurial motivation of students at SMK N 2 Magelang.